Penguatan Desa Wisata di Daerah Rawan Bencana Melalui Pemberdayaan Keberlanjutan Sosial dan Budaya: Pengabdian pada Volcano Tour Merapi di Kalurahan Umbulharjo, Cangkringan, Sleman, DI Yogyakarta - Suswanta, Suswanta; Ulfandari, Febrianti; Rahman, Denda Gita; Setiawan, Anang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This article explains the results of community service in disaster-prone areas, namely the Merapi Volcano Tour in Umbulharjo Village, Cangkringan, Sleman, DI Yogyakarta, which is based on social and cultural sustainability. The results of the discussion show that the natural potential of Mount Merapi, including forests, rivers affected by the eruption, agriculture, livestock, the house of the caretaker of the late Mbah Maridjan, the Kaliadem bunker, and the culture of the local community, have been successfully capitalized into leading tourist attractions. Tourism development is carried out by integrating traditions and cultures and involving the community in its management. This strategy based on social and cultural sustainability has proven effective, with the number of tourists in 2022 reaching 415,951 people, which contributes significantly to improving the economy of local residents. One of the results of this community service activity is the implementation of a workshop involving 25 residents, which aims to increase the capacity for participatory tourism management. This workshop provides training on social and cultural-based tourism management, while strengthening collaboration with the government and the private sector. However, several challenges still need to be addressed, such as improving road infrastructure and ensuring tourist safety given the difficult terrain, as well as the need for better collaborative strategies to preserve local culture and improve the quality of tourism services without damaging local cultural heritage.